PERBANDINGAN PENGARUH LATIHAN KNEE TUCK JUMP DAN JUMP AND FIX TERHADAP POWER OTOT TUNGKAI PADA SISWI YANG MENGIKUTI EKSTRAKURIKULER ATLETIK NOMOR LOMPAT JAUH SISWI KELAS X SMA NEGERI 7 PEKANBARU - Sitanggang, Frengki; Wijayanti, Ni Putu Nita; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that due to the lack of use of the leg strength in rejection, the results of the jumps achieved are on average 2-3 meters. This type of research is a form of Matching-Only Design research. that is, linking subjects together based on certain variables. The aim of this research was to compare the effect of knee jump and jump and fixt training on leg muscle strength. The population in this research consisted of 8 extracurricular students of class X athletic long jump at SMA Negeri 7 Pekanbaru. The sampling technique uses total sampling, where the total population is sampled. The data collection technique was obtained from the pre-test and the post-test in groups 1 and 2. The instrument in this research used the vertical power jump test as an instrument to measure leg muscle strength. The pre-test result data after calculating the LoMaks group 1 was 0.343 and the L table was 0.381, and the group 2 LoMaks was 0.222 and the L table was 0.381, this means that LoMaks is smaller than L table, there can be concluded that it is normally distributed. In the homogeneity test, data for groups 1 and 2 was 6.39. Given that Fcount (1.23) <of Ftable (6.39), it can be concluded that the two variances are homogeneous. The analysis was performed using t-test and F-test. Based on data analysis and discussion, the t-table value appears to be at the significant level of 0.05 1.943, this means that the value of tcount (2.333)> ttable (1.943) is the hypothesis that there is a difference in the effect is jumping off the knee ramp and jumping and fixating on muscle strength limbs of students undertaking athletic extracurricular activities in the long jump track of Class X SMA Negeri 7 Pekanbaru.Key Words: Knee Tuck Jump and Jump and Fix Exercises, Leg Muscle Strength